Finance and Development, December 1973. (Finance and Development; Finance and Development ;, 1973)
This paper reviews the population policy in developed countries. The paper highlights that despite the weakness of population concerns in most developed countries compared with less-developed countries, most of the former have taken certain actions that affect, or are thought to affect, demographic events. These actions include such measures as appointing official commissions to study the country's demographic situation and advise the government what to do; providing birth control services as part of the public health system; and so on. This paper also summarizes the conclusions drawn by Dr. Berelson from the 25 country reports.